2017
DOI: 10.1016/j.gie.2017.09.024
|View full text |Cite
|
Sign up to set email alerts
|

Pit pattern analysis with high-definition chromoendoscopy and narrow-band imaging for optical diagnosis of dysplasia in patients with ulcerative colitis

Abstract: Differentiation between non-neoplastic and neoplastic pit patterns in UC lesions shows a moderate to substantial agreement among expert endoscopists. The agreement for differentiating neoplastic from non-neoplastic lesions is significantly better for NBI in comparison with HD CE. The assessment of pit pattern I or II with nonmagnified HD CE or NBI has a high negative predictive value to rule out neoplasia. (Clinical trial registration number: NCT01882205.).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
46
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(47 citation statements)
references
References 22 publications
(42 reference statements)
0
46
0
1
Order By: Relevance
“…4). 15 The reasons for the lack of classifiable patterns are unclear, but this deficiency may reflect the continuing inflammation and the higher incidence of poorly differentiated and signet ring cancers 16 diagnosed in colonic IBD.…”
Section: Flat Lesion Without Protrusion Above the Mucosamentioning
confidence: 99%
“…4). 15 The reasons for the lack of classifiable patterns are unclear, but this deficiency may reflect the continuing inflammation and the higher incidence of poorly differentiated and signet ring cancers 16 diagnosed in colonic IBD.…”
Section: Flat Lesion Without Protrusion Above the Mucosamentioning
confidence: 99%
“…The classification commonly used to characterize visible lesions in IBD is the Kudo's classification [63]. Recent meta-analyses have suggested specific features (Kudo pit pattern type I or II, chromoendoscopy, or NBI) can be effective in enhancing the negative predictive value to 88 % -94 % [157,158]. Subsequent data using high definition dye-based chromoendoscopy and endoscopic trimodal imaging support this [159,160].…”
Section: Recommendationmentioning
confidence: 99%
“… 12 Recently, Bisschops et al . 11 used lesions retrieved from a randomized controlled trial comparing high-definition CE with NBI for the surveillance of colitis-associated dysplasia, and analyzed the diagnostic performance of pit patterns for predicting dysplasia. Carefully selected images of clearly visible lesions with visible pits were used in their study, and the sensitivity, specificity, and accuracy of neoplastic pit patterns for predicting dysplasia were 77%, 69%, and 72%, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…In the earliest study evaluating the role of CE for detecting dysplasia in UC, 6 Kudo pit patterns showed a 92% accuracy for differentiating between neoplastic and non-neoplastic lesions. However, in subsequent studies, Kudo pit patterns showed only 72% to 73% diagnostic accuracy for differentiating between neoplastic and non-neoplastic lesions in the colitis patients, 11 , 12 which would be inappropriate to use as indicators for dysplasia in the clinical practice. The relative inaccuracy of pit patterns for predicting colitis-associated dysplasia may be associated with diffuse and long-standing inflammatory changes in both the dysplasia and surrounding mucosa.…”
Section: Introductionmentioning
confidence: 99%